2020
DOI: 10.1177/2041669520981096
|View full text |Cite
|
Sign up to set email alerts
|

Semantic Congruency Modulates the Effect of Attentional Load on the Audiovisual Integration of Animate Images and Sounds

Abstract: Attentional processes play a complex and multifaceted role in the integration of input from different sensory modalities. However, whether increased attentional load disrupts the audiovisual (AV) integration of common objects that involve semantic content remains unclear. Furthermore, knowledge regarding how semantic congruency interacts with attentional load to influence the AV integration of common objects is limited. We investigated these questions by examining AV integration under various attentional-load … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 67 publications
0
2
0
Order By: Relevance
“…Previous studies have shown that incongruent stimuli have an effect on the modulation of multisensory integration ( Guo et al, 2015 ; Laurienti et al, 2004 ). Li et al (2020) used unisensory stimuli (animal images or sounds) and multisensory stimuli (semantically congruent audiovisual objects or semantically incongruent audiovisual objects) to assess multisensory integration. Results indicated that semantically incongruent animal sounds and images were not integrated ( Li et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that incongruent stimuli have an effect on the modulation of multisensory integration ( Guo et al, 2015 ; Laurienti et al, 2004 ). Li et al (2020) used unisensory stimuli (animal images or sounds) and multisensory stimuli (semantically congruent audiovisual objects or semantically incongruent audiovisual objects) to assess multisensory integration. Results indicated that semantically incongruent animal sounds and images were not integrated ( Li et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“… Li et al (2020) used unisensory stimuli (animal images or sounds) and multisensory stimuli (semantically congruent audiovisual objects or semantically incongruent audiovisual objects) to assess multisensory integration. Results indicated that semantically incongruent animal sounds and images were not integrated ( Li et al, 2020 ). More than that, the incongruent flankers conflicted with not only target arrow but also auditory stimuli in Experiment 2.…”
Section: Discussionmentioning
confidence: 99%